A CROSS-SECTIONAL STUDY ON THE USE OF TOPICAL CORTICOSTEROIDS AMONG PATIENTS VISITING OUTPATIENT DEPARTMENT (Journal of Medical & Health Sciences Review, 2025)
Objective: The aim of this study was to assess the magnitude of use of products containing topical steroids and their derivatives, the adverse effects stemming from their use, the motivation/cause of their use and the demographics of patients who used such products.Material and Methods: The design of this study was a cross-sectional study and this study was conducted at dermatology department DHQ Hospital Mirpur during the period of April 2023 to May, 2023. Preset questionnaires were filled out for patients who used topical steroid products on their face.Results: Out of 7740 patients who visited OPD, DHQ Hospital Mirpur, 384 patients presented symptoms of facial dermatosis.Conclusion: The application of Topical steroids on the face leads to a multitude of side effects and skin conditions. It is essential to create awareness among the patients as well as the doctors regarding the proper use of these drugs.